Brain spect in the pre-surgical evaluation of epileptic patients preliminary results - Carlos A. Buchpiguel; Arthur Cukiert; Fausto H. Hironaka; Giovani G. Cerri; Alvaro E. A. Magalhães; Raul Marino Jr. (Arquivos de Neuro-Psiquiatria)
Pre-surgical evaluation of epileptic patients consists of neurological examination, intensive electroencephalographic (EEG) monitoring and anatomical studies (CT and MRI). Functional methods such as PET and SPECT imaging are now used more frequently. We have studied pre-operatively 15 adult epileptic patients (8 female, 7 male) using a rotational scintillation camera interfaced to a dedicated computer. The tomographic images were obtained 15 minutes after intravenous injection of 99mTc_HMPAO. All had MRI scanning and intensive EEG monitoring which generally included seizure recording. Five patients had progressive lesions (3 meningiomas, 2 astrocytomas). In 10 patients, neuroradiological studies did not show the presence of progressive lesions (2 normal scans and 8 cases with inactive lesions). Two patients with meningioma showed hypoperfusion at the lesion site while the third patient had a marked hyperperfusion which might correlate with the clinical diagnosis of epilepsia partialis continua. In the astrocytoma patients SPECT scans showed hypoperfusion at the lesion site. Data obtained from the 10 patients without progressive CNS lesions showed: (a) in 4, SPECT findings correlated well with the anatomical findings; (b) in 5 instances, SPECT was able to disclose additional functional deficits; (c) in one case, there was no SPECT correlate of a discrete anatomical lesion. In 5 of these cases with no progressive lesions (n=10) SPECT findings were useful as a complementary tool in determining the clinical or surgical management of these patients. Despite the small number and hete-rogenicity of the present sample, SPECT seems to be an useful tool as part of the clinical workup of epileptic patients who are candidates for epilepsy surgery.